Contrasting effects of ocean warming on different components of plant-herbivore interactions. (September 2018) - Pagès, Jordi F.; Smith, Timothy M.; Tomas, Fiona; Sanmartí, Neus; Boada, Jordi; De Bari, Harriet; Pérez, Marta; Romero, Javier; Arthur, Rohan; Alcoverro, Teresa
Abstract: There is increasing uncertainty of how marine ecosystems will respond to rising temperatures. While studies have focused on the impacts of warming on individual species, knowledge of how species interactions are likely to respond is scant. The strength of even simple two-species interactions is influenced by several interacting mechanisms, each potentially changing with temperature. We used controlled experiments to assess how plant-herbivore interactions respond to temperature for three structural dominant macrophytes in the Mediterranean and their principal sea urchin herbivore. Increasing temperature differentially influenced plant-specific growth, sea urchin growth and metabolism, consumption rates and herbivore preferences, but not movement behaviour. Evaluating these empirical observations against conceptual models of plant-herbivore performance, it appears likely that while the strength of herbivory may increase for the tested macroalga, for the two dominant seagrasses, the interaction strength may remain relatively unchanged or even weaken as temperatures rise. These results show a clear set of winners and losers in the warming Mediterranean as the complex factors driving species interactions change. Highlights: Multiple mechanisms influence interactions, each likely modified by temperature. Mediterranean macrophyte-herbivore interactions show complex contrasts. Herbivory on the two main Mediterranean seagrasses is expected to decrease. A key canopy-forming macroalgae however is likely to suffer increased herbivory. Warming is creating winners and losers in temperate waters as interactions change.